Hadith #187 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) came to us at noon and water for ablution was brought to him. After he had performed ablution, the remaining water was taken by the people and they started smearing their bodies with it (as a blessed thing). The Prophet (ﷺ) offered two rak`at of the Zuhr prayer and then two rak`at of the `Asr prayer while a short spear (or stick) was there (as a Sutra) in front of him.
Grade: Sahih

Hadith #372 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
I saw Allah’s Messenger (ﷺ) in a red leather tent and I saw Bilal taking the remaining water with which the Prophet had performed ablution. I saw the people taking the utilized water impatiently and whoever got some of it rubbed it on his body and those who could not get any took the moisture from the others’ hands. Then I saw Bilal carrying a short spear (or stick) which he planted in the ground. The Prophet came out tucking up his red cloak, and led the people in prayer and offered two r
Grade: Sahih

Hadith #492 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) came out at midday and offered a two-rak`at Zuhr and `Asr prayers at Al-Batha and a short spear (or stick) was planted in front of him (as a Sutra). He performed ablution and the people took the remaining water left after his ablution and rubbed their bodies with it.
Grade: Sahih

Hadith #1897 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
The Prophet (ﷺ) made a bond of brotherhood between Salman and Abu Ad-Darda.’ Salman paid a visit to Abu Ad-Darda’ and found Um Ad-Darda’ dressed in shabby clothes and asked her why she was in that state. She replied, “Your brother Abu Ad-Darda’ is not interested in (the luxuries of) this world.” In the meantime Abu Ad-Darda’ came and prepared a meal for Salman. Salman requested Abu Ad- Darda’ to eat (with him), but Abu Ad-Darda’ said, “I am fasting.” Salman said, “I am
Grade: Sahih

Hadith #2922 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
I asked `Ali, “Do you have the knowledge of any Divine Inspiration besides what is in Allah’s Book?” `Ali replied, “No, by Him Who splits the grain of corn and creates the soul. I don’t think we have such knowledge, but we have the ability of understanding which Allah may endow a person with, so that he may understand the Qur’an, and we have what is written in this paper as well.” I asked, “What is written in this paper?” He replied, “(The regulations of) blood-money, the fre
Grade: Sahih

Hadith #3174 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
Ibn `Umar used to kill snakes, but afterwards he forbade their killing and said, “Once the Prophet (ﷺ) pulled down a wall and saw a cast-off skin of a snake in it. He said, ‘Look for the snake. ‘They found it and the Prophet (ﷺ) said, “Kill it.” For this reason I used to kill snakes. Later on I met Abu Lubaba who told me the Prophet (ﷺ) said, ‘Do not kill snakes except the short-tailed or mutilated-tailed snake with two white lines on its back, for it causes abortion and makes
Grade: Sahih

Hadith #3393 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
I saw the Prophet, and Al-Hasan resembled him.
Grade: Sahih

Hadith #3403 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
Once Allah’s Messenger (ﷺ) went to Al-Batha’ at noon, performed the ablution and offered’ a two rak`at Zuhr prayer and a two-rak`at `Asr prayer while a spearheaded stick was planted before him and the passersby were passing in front of it. (After the prayer), the people got up and held the hands of the Prophet and passed them on their faces. I also took his hand and kept it on my face and noticed that it was colder than ice, and its smell was nicer than musk.
Grade: Sahih

Hadith #3417 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
By chance I went to the Prophet (ﷺ) at noon while he was at Al-Abtah (resting) in a tent. Bilal came out (of the tent) and pronounced the Adhan for the prayer, and entering again, he brought out the water which was left after Allah’s Messenger (ﷺ) had performed the ablution. The people rushed to take some of the water. Bilal again went in and brought out a spear-headed stick, and then Allah’s Messenger (ﷺ) came out. As if I were now looking at the whiteness of his leg. Bilal fixed the
Grade: Sahih

Hadith #5133 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
The Prophet (ﷺ) cursed the lady who practices tattooing and the one who gets herself tattooed, and one who eats (takes) Riba’ (usury) and the one who gives it. And he prohibited taking the price of a dog, and the money earned by prostitution, and cursed the makers of pictures.
Grade: Sahih

Hadith #5184 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) said, “I do not take my meals while leaning (against something).
Grade: Sahih

Hadith #5185 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
While I was with the Prophet (ﷺ) he said to a man who was with him, “I do not take my meals while leaning.”
Grade: Sahih

Hadith #5560 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
I saw Bilal bringing a short spear (or stick) and fixing it in the ground, and then he proclaimed the Iqama of the prayer, and I saw Allah’s Messenger (ﷺ) coming out, wearing a cloak with its sleeves rolled up. He then offered a two-rak`at prayer while facing the stick, and I saw the people and animals passing in front of him beyond the stick.
Grade: Sahih

Hadith #5632 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
I came to the Prophet (ﷺ) while he was inside a red leather tent, and I saw Bilal taking the remaining water of the ablution of the Prophet, and the people were taking of that water and rubbing it on their faces; and whoever could not get anything of it, would share the moisture of the hand of his companion (and then rub it on his face).
Grade: Sahih

Hadith #5717 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
The Prophet (ﷺ) forbade the use of the price of blood and the price of a dog, the one who takes (eats) usury the one who gives usury, the woman who practises tattooing and the woman who gets herself tattooed.
Grade: Sahih

Hadith #5734 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
that he had bought a slave whose profession was cupping. The Prophet (ﷺ) forbade taking the price of blood and the price of a dog and the earnings of a prostitute, and cursed the one who took or gave (Riba’) usury, and the lady who tattooed others or got herself tattooed, and the picture-maker.
Grade: Sahih

Hadith #5907 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
The Prophet (ﷺ) established a bond of brotherhood between Salman and Abu Darda’. Salman paid a visit to Abu ad-Darda and found Um Ad-Darda’ dressed in shabby clothes and asked her why she was in that state.?” She replied, “Your brother, Abu Ad-Darda is not interested in the luxuries of this world.” In the meantime Abu Ad-Darda came and prepared a meal for him (Salman), and said to him, “(Please) eat for I am fasting.” Salman said, “I am not going to eat, unless you eat.” So A
Grade: Sahih

Hadith #6659 - Sahih al-Bukhari - Abu Juhaifa (Sahih al-Bukhari)
I asked `Ali “Do you have anything Divine literature besides what is in the Qur’an?” Or, as Uyaina once said, “Apart from what the people have?” `Ali said, “By Him Who made the grain split (germinate) and created the soul, we have nothing except what is in the Qur’an and the ability (gift) of understanding Allah’s Book which He may endow a man, with and what is written in this sheet of paper.” I asked, “What is on this paper?” He replied, “The legal regulations of Diya (B
Grade: Sahih